2018
DOI: 10.1186/s12870-018-1281-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought stress and water recovery on physiological responses and gene expression in maize seedlings

Abstract: BackgroundDrought is one of the major factors limiting global maize production. Exposure to long-term drought conditions inhibits growth and leads to yield losses. Although several drought-responsive genes have been identified and functionally analyzed, the mechanisms underlying responses to drought and water recovery treatments have not been fully elucidated. To characterize how maize seedling respond to drought stress at the transcriptional level, we analyzed physiological responses and differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(139 citation statements)
references
References 56 publications
9
108
0
1
Order By: Relevance
“…Transcriptome analysis confirms the negative impact of the imposed drought stress on leaf growth and development (Zhang et al, ): among the 2,751 DEGs identified at the end of the stress treatment, the 1,957 stress down‐regulated genes are indeed enriched in functional terms associated to cell cycle regulation, growth and cell wall biosynthesis, indicating the inhibition of both cell division and expansion rates during water deprivation. Many of these genes were previously found down‐regulated in the maize leaf growth zone after mild and severe drought stresses (Avramova et al, ; Granier, InzĂ©, & Tardieu, ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Transcriptome analysis confirms the negative impact of the imposed drought stress on leaf growth and development (Zhang et al, ): among the 2,751 DEGs identified at the end of the stress treatment, the 1,957 stress down‐regulated genes are indeed enriched in functional terms associated to cell cycle regulation, growth and cell wall biosynthesis, indicating the inhibition of both cell division and expansion rates during water deprivation. Many of these genes were previously found down‐regulated in the maize leaf growth zone after mild and severe drought stresses (Avramova et al, ; Granier, InzĂ©, & Tardieu, ).…”
Section: Discussionmentioning
confidence: 68%
“…However, in studies published so far, osmotic stress has been mostly simulated in vitro by the addition of polyethylene glycol (PEG) or, when plants have been grown in soil, they have been sampled at seedling stage soon after hours of air‐drying or a few days of drought treatment (Ding et al, ; Jia et al, ; Lu et al, ; Opitz et al, ; Shan et al, ; Wu, Ning, Zhang, Wu, & Wang, ). In addition, only a few studies have addressed the genetic and epigenetic regulation of traits for tolerance/susceptibility to drought considering recovery as a real component of environmental challenges in the field (Zhang, Lei, Lai, Zhao, & Song, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the enriched GO terms, common drought‐related terms typically recovered in drought stress experiments (Fracasso et al, ; Wu et al, ; Zhang, Lei, Lai, Zhao, & Song, ) were recovered here using both control types. For up‐regulated genes, “response to water deprivation (GO:0009414)” and “response to water (GO:0009415)” were over‐represented on all days before recovery in both species.…”
Section: Resultsmentioning
confidence: 80%
“…For most time points, however, there was considerable overlap in enriched GO terms based on the different control types, and the rank order of these shared GO terms based on FDR was highly similar (Figure ). For up‐regulated genes, for example, shared terms included essential drought‐related terms such as “response to water deprivation (GO:0009414),” “response to abiotic stress (GO:0009628)” and “response to abscisic acid (GO:0009737)” (Fracasso et al, ; Wu et al, ; Zhang et al, ). For nonshared GO terms, when using the TC control type, “secondary metabolic process (GO: 0019748)” was over‐represented on Day 3, Day 4, and Day 5 in P. notatum and “response to external stimulus (GO:0009605)” was over‐represented on Day 3 and Day 4 in P. juergensii .…”
Section: Discussionmentioning
confidence: 99%
“…Previous results showed that boron (B) and silicon (Si) application could induce physiological resistance of oil palm seedlings to drought stress [32]. The genes involved in cellular nitrogen compound metabolic processes and transmembrane transport are differentially expressed during drought treatments [33]. Therefore, we investigated the expression pattern of the amino acid permease genes in the root and leaf tissues in E. guineensis in response to PEG treatment by using qRT-PCR ( Figure 5).…”
Section: Cold Stress Effects On the Expression Profiles Of Amino Acidmentioning
confidence: 99%